Development of Learning Media Based on Autoplay Chemistry to Improve Students’ Communicative Characters on Chemistry - Erna, Maria; Irfandi, Irfandi; Rasmiwetti, Rasmiwetti (JTP - Jurnal Teknologi Pendidikan, 2021)
The implementation of learning media based on ICT (Information and Communication Technology) on chemistry was found to be very low. For this reason, ICT-based chemistry learning media which utilized autoplay application were developed in this research. The validated product of the learning media based by autoplay on chemistry can be implemented as a learning medium to improve students’ communicative character. This research was designed by using the Plomp model in the form of Research and Development (R&D). Data of this research were collected by validation sheets, questionnaire responses (teachers and students), and communicative observation sheets with descriptive statistical analyses and independent sample t test. The validity results showed that the average percentage from media expert and material expert judgment were 88.25% and 91.69% with a category of valid. Moreover, the results of the response of teachers and students respectively obtained an average percentage score of 85% and 81% with a category of very interesting. Then, the results of the independent sample t test for 0,000 <0.05 indicated that there were significant differences in the communicative character of students before and after the use of learning media based on autoplay on chemistry with a percentage of 72.25%.